UNDERPRICING PHENOMENON ON INITIAL PUBLIC OFFERING ON THE INDONESIA STOCK EXCHANGE 2013-2017 - Sofiati Khairunnisaa; Meina Wulansari Yusniar, Asrid Juniar (INTERNATIONAL JOURNAL OF ECONOMIC LITERATURE, 2025)
This study examines the phenomenon of underpricing in Initial Public Offering (IPO) on the Indonesia Stock Exchange for the period 2013-2017. This study uses a quantitative method with an exploratory approach, involving 59 companies selected through purposive sampling. The variables studied include Debt to Equity Ratio (DER), Return on Equity (ROE), auditor reputation, fractional holding, company age, company size, and proceeds. Data analysis was carried out through classical assumption tests and multiple linear regression. The results showed that only auditor reputation and fractional holding variables had a significant effect on underpricing. High auditor reputation gives investors confidence, while fractional holding affects information asymmetry between management and investors. Other variables, such as DER, ROE, company age, company size, and proceeds, do not have a significant effect. This study provides insights for issuers and investors to understand the factors that influence stock underpricing, and encourages further research by expanding the variables and study period.